ANALYSIS STEGO-IMAGE EXTRACTION USING ROT13 AND LEAST SIGNIFICANT BIT (LSB) ALGORITHM METHOD ON TEXT SECURITY - Hillman Akhyar Damanik; Merry Anggraeni; Tomi Defisa (Jurnal Ilmiah FIFO, 2017)
Cryptography is both a science and an art to keep the message confidential. While steganography is the science and art of hiding secret messages in other messages so that the existence of such secret messages is unknowable and generally serves to disguise the existence of confidential data making it difficult to detect and protect the copyright of a product. Steganography requires two properties, namely container media and secret messages. The application of steganographic and cryptographic combination is done by Least Significant Bit (LSB) and ROT13 algorithm. Steganography with the LSB method is one of the methods used to hide messages on digital media by inserting it to the lowest bits or the most right bits of the pixel data that compile the file. In this research, the authors propose the technique of securing Steganography secret messages with layered security, by adding Cryptography to secret messages that will be inserted into digital images and then messages inserted into digital images through Steganography using LSB method.